Business Group Program Performance on Poverty Elevation - Murtiwidayanti, Sri Yuni; Hidayatullah, A Nururrochman (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research means to reveal business group (Kube) seen from social, economic, and institutional aspects, including its benefit to the members of the poor community, its handicap and supporting factors. This research is qualitative-descriptive approach. Data resources are from eight business groups, the informants are rural local officials from related institution, social guides, social volouteers, informal leaders, women caders, cooporational partners, and community members form Kupang Municipality and Regency. Data are gathered through interview, observation, and documentary analysis. Data are analysed through interpretive-descriptive technik. The result shows that kubes are in developing category. If they seen form social performance aspect, five kubes have good score, three kubes have sufficient score, seen from social aspect there are five kubes have good score, three kubes have sufficient score. If they seen seen from institutional aspect, one kube has good score, and three kubes have sufficient score, and four Kubes have poor score. kube as a mean of empowerment and poverty elevation should improve its performance so that kube as a business group can be achieved. Kube can be economic institution that based on the spirit of togetherness and solidarity, national loyalty, that it can improve lives and social welfare qualities.